PENGARUH SOCIAL COMPARISON TERHADAP PSYCHOLOGICAL WELL BEING PADA REMAJA PENGGUNA TIKTOK - Jundi Jundulloh; Muhammad Muhajirin; Anandha Putri Rahimsyah (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This study aims to examine the effect of social comparison on psychological well-being among adolescent active users of TikTok. Social comparison is defined as the process through which individuals evaluate themselves by comparing their opinions, abilities, and characteristics with those of others, while psychological well-being refers to optimal psychological functioning, including self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. This research employs a quantitative approach with a correlational design. The participants consisted of Grade X and XI students of SMA Muhammadiyah Singaparna who actively use TikTok. Data were collected using INCOM (The Iowa-Netherlands Comparison Orientation Measure) and Ryff’s Psychological Well-Being Scale, and analyzed using Pearson correlation and simple linear regression.The results indicate a significant negative relationship between social comparison and psychological well-being, meaning that higher levels of social comparison are associated with lower psychological well-being among adolescents. Regression analysis shows an R value of 0.569, indicating a moderate relationship between variables. The R² value of 0.323 indicates that 32.3% of the variance in psychological well-being is explained by social comparison, while 67.7% is influenced by other factors. These findings suggest that exposure to idealized social media content may encourage unrealistic self-evaluations, which can reduce adolescents’ psychological well-being.